2016
DOI: 10.3390/rel7060061
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Analysis of Spiritual Care Based on Islamic Sources

Abstract: Abstract:The cultural and religious resources of every community influence the definition of spiritual care. This paper discusses a concept analysis of spiritual care in an Islamic context. The Quran, narrations (Shie'h) and commentarial books were searched, for information data. The data was used to provide a comprehensive definition of the concept of spiritual care from Islamic literature. We identified the attributes, antecedents and consequences of spiritual care according to Roger's concept analysis appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
1
21
0
3
Order By: Relevance
“…In this study, the educational content retrieved from previous studies [31][32][33][34][35] included spiritual issues such as familiarity with spirituality, professional dimension and improving the quality of life, study and implementation of spiritual care, communication skills, attention to the human dignity and personal support, counseling, hope and hope therapy, and communication with the patient. It was presented by lessons of lecture and small group discussions in seven 60 min group sessions during a single month (Box 1).…”
Section: Interventionmentioning
confidence: 99%
“…In this study, the educational content retrieved from previous studies [31][32][33][34][35] included spiritual issues such as familiarity with spirituality, professional dimension and improving the quality of life, study and implementation of spiritual care, communication skills, attention to the human dignity and personal support, counseling, hope and hope therapy, and communication with the patient. It was presented by lessons of lecture and small group discussions in seven 60 min group sessions during a single month (Box 1).…”
Section: Interventionmentioning
confidence: 99%
“…This therapy can improve the patient's sleep quality, enthusiasm for creativity and increase confidence to engage in social relations with others (Cita, 2016). Marzband (2016) reviewed Quran and Shie'h's narrations (Hadiths), and found the concept of spiritual care. The research suggested that spiritual care involves spiritual capacities or skills to help patients in achieving purified life (Hayate-tayebeh).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, religious beliefs and practices also helped them realize the risk of tuberculosis transmission. They facilitated the participants’ understanding of the disease and provided meaning to the disease [50,51] and hope to deal with their fear associated with it [51]. Therefore, religion played an important role in disease prevention [50].…”
Section: Discussionmentioning
confidence: 99%